Anaerobic radical enzymes for biotechnology - Jäger, Christof M.; Croft, Anna K. (Wiley, 2018)
Enzymes that proceed through radical intermediates have a rich chemistry that includes functionalisation of otherwise unreactive carbon atoms, carbon-skeleton rearrangements, aromatic reductions, and unusual eliminations. Especially under anaerobic conditions, organisms have developed a wide range of approaches for managing these transformations that can be exploited to generate new biological routes towards both bulk and specialty chemicals. These routes are often either much more direct or allow access to molecules that are inaccessible through standard (bio)chemical approaches. This review gives an overview of some of the key enzymes in this area: benzoyl-CoA reductases (that effect the enzymatic Birch reduction), ketyl radical dehydratases, coenzyme B12-dependant enzymes, glycyl radical enzymes, and radical SAM (AdoMet radical) enzymes. These enzymes are discussed alongside biotechnological applications, highlighting the wide range of actual and potential uses. With the increased diversity in biotechnological approaches to obtaining these enzymes and information about them, even more of these amazing enzymes can be expected to find application in industrial processes.